(3fRgI GdCQhGM hQhVI GdCaQGMs - (3eMeO Hf eMehO GdETQGbj GdTgQRhQj , TeS GdOjf,J (B687 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdCRdi CeG HYO aEf JhGQjN GdMceGA GdCbOejf hGdadGSaI GdeJCdgjf ef GdjhfGfjjf hGdeUQjjf eeG jLH Ydi GdeSJHUQ JMUdg s
(3BNQgG (B:s
(3hbGd GPcQi CjgG GdeOjfI GdaGVdI HCUhGJc GdLGeYI cja jchf cJGH Gddg eTghOkG jQg GdZGadhf Je HJhajb Gddg s
(3GdcJGH ai JhGQjN GdMceGA hGTJed Ydi (B111 (3JQLeI ef GdeJbOejf hGdeJCNQjfs
(3HgG fXGe GdJYbjHIs
(3ai GdeYgO fSN CNQi HQbe (B542 / 848 / 1082 / 1278 (3JGQjN hai HQhcdeGf (B1/ 617 (3QhVI GdGaQGM hfRgI GdCQhGM hHChd gPg GdfSNI Cfg GdYbO GdaQjO ai JGQjN HYV GdMceGA Gdes
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs